Pengaruh Citra Merek Dan Kualitas Ulasan Online Terhadap Minat Beli Pengguna Shopee Di Kota Cirebon - Zaki Januar Mulyawan; Aang Curatman (Universitas Muhammadiyah Palembang, 2026)
This study aims to analyze the influence of brand image and online reviews on the purchase intention of Shopee users in Cirebon City, both partially and simultaneously. This research method uses quantitative. The population in this study are Shopee application users in Cirebon City who have used the application for more than six months. The sampling technique used purposive sampling with a total of 120 respondents. Data collection was carried out through questionnaires, while data analysis used the Partial Least Square–Structural Equation Modeling (PLS-SEM) method with the help of the SmartPLS 4 program. The results showed that brand image has a positive and significant effect on purchase intention, with a t-statistic value of 5.046 and a significance level of 0.000 <0.05. Online reviews also have a positive and significant effect on purchase intention, with a t-statistic value of 5.564 and a significance level of 0.000 <0.05. In addition, brand image has a positive and significant effect on online reviews, as indicated by a t-statistic value of 277.524 and a significance level of 0.000 < 0.05. Simultaneously, brand image and online reviews have a very strong influence on Shopee users' purchase intention, with a coefficient of determination (R²) value of 0.959. This indicates that 95.9% of the variation in purchase intention can be explained by brand image and online reviews, while the rest is influenced by other factors outside the study. The conclusion of this study is that brand image and online reviews are the main factors influencing Shopee users' purchase intention in Cirebon City. Therefore, marketplaces and sellers are advised to continue strengthening their brand image and optimally manage online reviews to increase purchase intention and consumer trust..